Potato starch residue reinforced PBAT degradable injection molding material and preparation method and application thereof
By drying, crushing and modifying the potato starch residue, and melting and blending it with PBAT, the difficulty of using potato starch residue in the production of biodegradable plastics is solved, and a degradable injection molded material with excellent mechanical properties and thermal stability is prepared, realizing the recycling of resources.
Patent Information
- Application Number
- CN202411919244.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Due to its high moisture content and perishability, potato starch residue is difficult to be effectively used in the production of biodegradable plastics, resulting in difficulties in forming, processing and storage and transportation.
Potato starch residue is prepared by drying, crushing, sieving and modification, and melt blending with thermoplastic biodegradable plastic PBAT to prepare potato starch residue enhanced PBAT degradable injection molded materials.
It realizes the effective utilization of potato starch residue, prepares biodegradable plastics with excellent mechanical properties and thermal stability, and improves the tensile strength and thermal stability of the material, and has good recycling performance.
Smart Images

Figure CN119752126A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plastic production, and in particular to a potato starch residue reinforced PBAT biodegradable injection molding material, a preparation method and an application thereof. Background Art
[0002] Biodegradable plastics are materials with excellent performance and can be completely decomposed by environmental microorganisms after being discarded. As the problem of plastic pollution becomes increasingly serious, the research and development and application of degradable plastic materials are receiving more and more attention. Thermoplastic biodegradable plastic PBAT, as a biodegradable plastic, has been widely studied due to its good processing performance and biodegradability. At the same time, natural polymers such as cellulose and starch are abundant in nature, low in price, and renewable. The biopolymer materials prepared from them have good biocompatibility, can be completely degraded, and are safe and non-toxic. They have attracted attention from various countries due to their dual significance of fully utilizing natural renewable resources and environmental governance. However, most of them are not thermoplastic, difficult to mold and process, and have poor water resistance, which limits their application.
[0003] In the prior art, the Chinese invention patent with application number 202110561417.5 discloses a method for producing degradable plastics from bagasse, comprising the following steps: S1 takes the following raw materials by weight: 60-100 parts of modified bagasse, 20-30 parts of filler, 0.5-1 part of C5 petroleum resin, 2-6 parts of polyacrylate, 3-6 parts of plasticizer, 2-4 parts of coupling agent, 0.1-0.3 parts of dispersant; S2 raw material pretreatment: put the above raw materials into a high-speed mixer and mix them evenly, stirring and mixing, the stirring speed is 850-1500r / min, and the time is 15-25min; S3 melt blend the mixed materials to obtain a uniformly mixed blend; S4 add the blend obtained in the previous step to a twin-screw extruder, extrude and granulate, and obtain a degradable plastic finished product. The tensile strength of the obtained degradable plastic finished product is 11.53-12.93MPa.
[0004] Potato starch residue is a byproduct produced during potato processing. It is mainly composed of starch, cellulose, hemicellulose, pectin, protein, free amino acids, minerals and fat, etc., and has a potential reinforcing effect. However, the moisture content of fresh potato residue can be as high as 90% or more, which makes it present a slurry material property, and there is a certain combination of water with fiber and pectin, which makes it difficult to remove water and has a high drying cost. In addition, due to the presence of various microorganisms, potato residue is easy to rot and deteriorate, and is not easy to store and transport, which increases the difficulty of development and reuse. In my country, the output of potatoes is very large, and the potato starch residue produced during potato processing is also relatively large. How to apply this part of potato starch residue to the production of biodegradable plastics, prepare biodegradable plastics with excellent mechanical properties and thermal stability, and realize the recycling of resources at the same time, has a very positive and important significance. Summary of the invention
[0005] Based on this, the present invention provides a potato starch residue reinforced PBAT biodegradable injection molding material and a preparation method thereof, so as to apply this part of potato starch residue to the production of biodegradable plastics, prepare biodegradable plastics with excellent mechanical properties and thermal stability, and realize the recycling of resources at the same time.
[0006] The technical solution of this application to solve the above technical problems is as follows:
[0007] A method for preparing a potato starch residue reinforced PBAT biodegradable injection molding material comprises the following steps:
[0008] S10. The potato starch residue is dried, crushed and sieved to obtain pretreated potato starch residue;
[0009] S20. Adding a silane coupling agent solution to the pretreated potato starch residue, stirring and drying to obtain a modified potato starch residue;
[0010] S30. The modified potato starch residue and PBAT are mixed uniformly in a weight ratio of (1:9) to (6:4) to obtain a mixture;
[0011] S40. melt-blending the mixture, controlling the blending temperature at 100 to 135° C., blending for 10 to 20 minutes and then cooling to obtain a potato starch residue reinforced PBAT biodegradable injection molding material.
[0012] Preferably, in the above preparation method, in step S10, the potato starch residue is sieved with a mesh size of 50 to 150 meshes.
[0013] Preferably, in the above preparation method, in step S20, the preparation method of the silane coupling agent solution is:
[0014] A silane coupling agent is added into a mixed solution of anhydrous ethanol and distilled water to obtain the silane coupling agent solution; wherein in the mixed solution of anhydrous ethanol and distilled water, the volume ratio of the anhydrous ethanol to the distilled water is (8 to 10):1.
[0015] Preferably, in the above preparation method, in step S20, the weight ratio of the pretreated potato starch residue to the silane coupling agent in the silane coupling agent solution is (15 to 20):1.
[0016] Preferably, in the above preparation method, the silane coupling agent is 3-aminopropyltriethoxysilane.
[0017] Preferably, in the above preparation method, in step S30, the weight ratio of the pretreated potato starch residue to the PBAT is (5:5) to (6:4).
[0018] A potato starch residue reinforced PBAT biodegradable injection molding material is prepared by the above-mentioned method for preparing the potato starch residue reinforced PBAT biodegradable injection molding material.
[0019] An application of the above-mentioned potato starch residue reinforced PBAT biodegradable injection molding material in the preparation of biodegradable plastic products.
[0020] The above solution adopted by this application has at least the following beneficial effects:
[0021] The present application provides a method for preparing a potato starch residue reinforced PBAT degradable injection molding material (hereinafter referred to as degradable injection molding material). The potato starch residue is first dried, crushed and sieved to obtain pretreated potato starch residue; then a silane coupling agent solution is added to the pretreated potato starch residue, stirred evenly and dried to obtain modified potato starch residue; then the modified potato starch residue is mixed evenly with a thermoplastic biodegradable plastic (PBAT) in a weight ratio of (1:9) to (6:4) to obtain a mixture; finally, the mixture is melt-blended, the blending temperature is controlled at 100 to 135° C., and the mixture is cooled after blending for 10 to 20 minutes to obtain a potato starch residue reinforced PBAT degradable injection molding material. When the weight ratio of the pretreated potato starch residue to PBAT is 6:4, the tensile strength of the prepared degradable injection molding material sample after injection molding can reach 14.9 MPa, which has good mechanical properties. While obtaining high-performance injection molding materials, a large amount of potato starch residue is added to achieve resource recycling; according to differential scanning calorimetry (DSC) analysis, the glass transition temperature and melting temperature of the degradable injection molding material of the present application are higher than those of pure PBAT, indicating that the material has good thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A bar graph showing the tensile strength of biodegradable injection molding materials.
[0024] Figure 2 This is a curve chart of the cooling of the biodegradable injection molding material after the first heating.
[0025] Figure 3 This is a curve chart of the second temperature rise after heating and cooling of the biodegradable injection molding material. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The technical solution of the present invention will be further described below in conjunction with the drawings of the embodiments of the present invention, and the present invention is not limited to the following specific implementation methods.
[0027] It should be understood that the same or similar reference numerals in the drawings of the embodiments correspond to the same or similar components. In the description of the present invention, it should be understood that if there are terms such as "upper", "lower", "front", "rear", "left", "right", "top", "bottom" and the like indicating an orientation or positional relationship, it is based on the orientation or positional relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the positional relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0028] In a specific embodiment, a method for preparing a potato starch residue reinforced PBAT biodegradable injection molding material comprises the following steps:
[0029] S10. The potato starch residue is dried, crushed and sieved to obtain pretreated potato starch residue;
[0030] Potato starch residue is a byproduct produced during potato processing, mainly composed of starch, cellulose, hemicellulose, pectin, protein, free amino acids, minerals and fat, etc., and has a potential reinforcing effect, but the moisture content of fresh potato residue can be as high as more than 90%, so it needs to be dried before use. At the same time, since the potato starch residue particles are of different sizes, direct use will affect the morphology and performance of the prepared degradable injection molding material, so the dried potato starch residue is crushed and then sieved, and preferably, the potato starch residue is sieved with a mesh number of 50 to 150.
[0031] S20. Adding a silane coupling agent solution to the pretreated potato starch residue, stirring and drying to obtain a modified potato starch residue; wherein the preparation method of the silane coupling agent solution is: adding a silane coupling agent to a mixed solution of anhydrous ethanol and distilled water to obtain the silane coupling agent solution; wherein in the mixed solution of anhydrous ethanol and distilled water, the volume ratio of the anhydrous ethanol to the distilled water is (8 to 10): 1. In this step, the mixed solution of anhydrous ethanol and distilled water mainly acts as a solvent, that is, it is used to dissolve the silane coupling agent, and the amount of the silane coupling agent solution added should be based on the pretreated potato starch residue being able to be uniformly mixed with the silane coupling agent, and the weight ratio of the pretreated potato starch residue to the silane coupling agent in the silane coupling agent solution is (15 to 20): 1. By using silane coupling agents, a "molecular bridge" can be built between the interfaces of inorganic and organic substances, connecting two materials with very different properties together to improve the performance of the composite material and increase the bonding strength. The silane coupling agent in this application is preferably 3-aminopropyltriethoxysilane (KH550), also known as: γ-aminopropyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-APTS. The chemical formula NH2CH2CH2CH2Si(OC2H5)3 is an amino functional silane, which is alkaline. The appearance is a colorless or slightly yellow transparent liquid with strong versatility. The KH550 molecule contains two different active groups-amino and oxygen groups, which are used to couple organic polymers and inorganic fillers, enhance their adhesion, and improve the mechanical, electrical, water-resistant, and anti-aging properties of the product.
[0032] S30. The modified potato starch residue and PBAT are mixed uniformly in a weight ratio of (1:9) to (6:4) to obtain a mixture; preferably, the weight ratio of the pretreated potato starch residue to the PBAT is (5:5) to (6:4). Experiments show that with the increase in the amount of pretreated potato starch residue added, the tensile strength of the sample decreases first and then increases, and the average value of 13.33Mpa is still higher than the tensile strength of the degradable plastic produced from bagasse in the background technology. However, when the mass ratio of the pretreated potato starch residue to PBAT is 7:3, the two cannot be mixed and melted together, and the preparation process cannot be met. When the weight ratio of the pretreated potato starch residue to PBAT is 6:4, the tensile strength of the sample of the prepared degradable injection molding material after injection molding can reach 14.9MPa, which has good mechanical properties. While obtaining high-performance injection molding materials, a large amount of potato starch residue is added to achieve resource recycling.
[0033] S40. The mixture is melt blended, the blending temperature is controlled at 100 to 135°C, and the mixture is cooled after blending for 10 to 20 minutes to obtain a potato starch residue reinforced PBAT degradable injection molding material. Specifically, the mixture is melt blended in an internal mixer for 10 to 20 minutes, the blending temperature in zone 1 is controlled at 135°C, and the blending temperature in zone 2 is controlled at 100°C, and the blended material is cooled to obtain a potato starch residue reinforced PBAT degradable injection molding material.
[0034] In another specific embodiment of the present application, a potato starch residue reinforced PBAT degradable injection molding material is prepared by the above-mentioned method for preparing the potato starch residue reinforced PBAT degradable injection molding material.
[0035] In another specific embodiment of the present application, a potato starch residue-reinforced PBAT biodegradable injection molding material is used in the preparation of biodegradable plastic products.
[0036] It is worth noting that the process temperature and process time designed in the above-mentioned implementation manner are both a temperature or time used in the experimental process. Those skilled in the art can make reasonable adjustments within the error range based on the process temperature and process time provided by the present invention, which should be included in the protection scope of the present invention.
[0037] The technical solution and technical effects of the present invention are further illustrated below through specific experimental examples.
[0038] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0039] 1. Main reagents
[0040] It should be noted that in the examples of the present invention, all reagents and solvents are commercially available and can be used without further purification.
[0041] 2. Blank example
[0042] The PBAT material was directly injection molded with an injection heating temperature of 225°C, a pressure of 0.5MPa, and a holding time of 15s to prepare the required samples.
[0043] 3. Comparative ratio
[0044] 10.56 parts of potato starch residue were taken, dried and crushed, sieved through 100 mesh, and then mixed with 100 parts of PBAT; the mixture was melt-blended in an internal mixer for 15 minutes, and the blending temperature in zone one was controlled at 135°C and that in zone two was controlled at 100°C; the blended material was cooled to obtain a PBAT degradable injection molding material; the PBAT degradable injection molding material was injection molded, with an injection heating temperature of 225°C, a pressure of 0.5 MPa, and a holding time of 15s to prepare the required sample.
[0045] 4. Example 1: Exploring the effect of modified potato starch residue on the performance of biodegradable injection molding materials
[0046] 10.56 parts of potato starch residue were taken, dried and crushed, and sieved through 100 mesh to obtain pretreated potato starch residue; a silane coupling agent solution was added to the pretreated potato starch residue, stirred evenly and then dried, wherein the silane coupling agent solution contained 0.56 parts of silane coupling agent KH550, 17.3 ml of anhydrous ethanol and 1.9 ml of distilled water; then the pretreated potato starch residue was mixed with 100 parts of PBAT; the mixture was melt-blended in an internal mixer for 15 minutes, and the blending temperature in zone one was controlled at 135° C. and in zone two was controlled at 100° C.; the blended material was cooled to obtain a PBAT degradable injection molding material; the PBAT degradable injection molding material was injection molded, the injection molding heating temperature was 225° C., the pressure was 0.5 MPa, and the holding time was 15 s, to prepare the required sample, which was marked as sample 1.
[0047] The mechanical properties of the samples of the blank example, comparative example and embodiment 1 were tested, and the test results are as follows:
[0048] Table 1 Tensile strength of blank example, comparative example and embodiment 1
[0049] sample Tensile strength(Mpa) Blank example 22.5 Comparative Example 12.1 Sample 1 17.5
[0050] As can be seen from Table 1, when unmodified potato starch residue is directly added to the PBAT material, the tensile strength and impact strength of the obtained sample of the injection-molded degradable injection molding material, that is, the comparative sample, are greatly reduced. It can be seen that the potato starch residue cannot be directly applied to the preparation of the degradable injection molding material. In Example 1, the potato starch residue is modified with a silane coupling agent solution, and the modified potato starch residue and PBAT are used to prepare the degradable injection molding material. It can be seen from the mechanical property test that the tensile strength of sample 1 is 17.5Mpa, which is significantly improved compared with the comparative sample. At the same time, the tensile strength of the degradable plastic produced by using bagasse in the background technology is also increased by 4.57 to 5.97Mpa, and the improvement rate is 35.34% to 51.78%.
[0051] 5. Example 2: Exploring the effect of the amount of modified potato starch residue added on the performance of biodegradable injection molding materials
[0052] The potato starch residue was taken as shown in Table 2, dried and crushed, and sieved through 100 mesh to obtain pretreated potato starch residue; a silane coupling agent solution was added to the pretreated potato starch residue, stirred evenly and dried, wherein the silane coupling agent solution contained silane coupling agent KH550, anhydrous ethanol and distilled water in an amount shown in Table 2; and then mixed with the weight portions of PBAT shown in Table 2; the mixture was melt blended in an internal mixer for 15 minutes, and the blending temperature in zone 1 was controlled at 135° C. and in zone 2 at 100° C.; the blended material was cooled to obtain a PBAT degradable injection molding material; the PBAT degradable injection molding material was injection molded, and the injection molding heating temperature was 225° C., the pressure was 0.5 MPa, and the holding time was 15 s to prepare the required samples, which were marked as samples 2 to 7.
[0053]
[0054] Table 2 Amounts of raw materials used in samples of Example 2
[0055] Note: The content of potato starch residue after pretreatment = weight of potato starch residue after pretreatment / (weight of potato starch residue after pretreatment + weight of PBAT) × 100%.
[0056] The mechanical properties of the samples of the above-mentioned embodiment 2 were tested, and the test results are as follows:
[0057] Table 3 Tensile strength of Example 2
[0058]
[0059]
[0060] Please refer to Table 3 and combine Figure 1, with the increase of the amount of pretreated potato starch residue added, the tensile strength of the sample showed a trend of first decreasing and then increasing, and the average value of 13.33Mpa was still higher than the tensile strength of the degradable plastic produced with bagasse in the background technology. The tensile strength of sample 6 was 14.9Mpa, which was significantly improved compared with the samples of the comparative example. At the same time, it was also increased by 1.97 to 3.37Mpa compared with the tensile strength of the degradable plastic produced with bagasse in the background technology, with an increase rate of 15.23% to 29.22%. It should be noted that when the mass ratio of the pretreated potato starch residue to PBAT is 7:3, the two cannot be mixed and melted together, and the preparation process cannot be met.
[0061] 6. Thermal stability test
[0062] Differential scanning calorimetry (DSC) was used to evaluate the thermal stability of the samples. The experimental data were obtained using DSC Q1000 from TA Instruments according to the DSC test method in ISO 11357.
[0063] See also Figure 2 and Figure 3 , the glass transition temperature Tg of pure PBAT is 42.48℃. After adding potato starch residue, its Tg increases significantly, reaching a maximum of 47.53℃. The glass transition temperature of the material is related to the temperature resistance of the product. The higher the Tg, the better the temperature resistance of the processed product. The reason for the increase in Tg is mainly due to the addition of modified potato starch residue into the flexible PBAT molecular chain. The two are cross-linked, and the network structure formed increases the rigidity of the molecular chain of the composite material, thereby increasing the glass transition temperature.
[0064] The melting temperature of pure PBAT material is 120.83°C, and the addition of potato starch residue directly increases the melting temperature of the sample to 126.17°C. The main reason for this phenomenon is that the free -OH in the modified potato starch residue forms hydrogen bonds with the PBAT molecular chain, which increases the enthalpy value and thus increases the melting temperature.
[0065] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a potato starch residue reinforced PBAT biodegradable injection molding material, characterized in that: The following steps are involved: S10. The potato starch residue is dried, crushed and sieved to obtain pretreated potato starch residue; S20. Adding a silane coupling agent solution to the pretreated potato starch residue, stirring and drying to obtain a modified potato starch residue; S30. Mixing the modified potato starch residue with PBAT in a weight ratio of (1:9) to (6:4) Mixing evenly to obtain a mixture; S40. melt-blending the mixture, controlling the blending temperature at 100 to 135° C., blending for 10 to 20 minutes and then cooling to obtain a potato starch residue reinforced PBAT biodegradable injection molding material.
2. The preparation method according to claim 1, characterized in that: In step S10, the potato starch residue is sieved with a mesh size of 50 to 150 meshes.
3. The preparation method according to claim 1, characterized in that: In step S20, the preparation method of the silane coupling agent solution is: A silane coupling agent is added to a mixed solution of anhydrous ethanol and distilled water to obtain the silane coupling agent solution; wherein in the mixed solution of anhydrous ethanol and distilled water, the volume ratio of the anhydrous ethanol to the distilled water is (8 to 10):
1.
4. The preparation method according to claim 3, characterized in that: The amount of the silane coupling agent added is 25 to 35 parts per liter of the mixed solution of anhydrous ethanol and distilled water.
5. The preparation method according to claim 1, characterized in that: In step S20, the weight ratio of the pretreated potato starch residue to the silane coupling agent in the silane coupling agent solution is (15 to 20):
1.
6. The preparation method according to claim 3, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane.
7. The preparation method according to claim 1, characterized in that: In step S30, the weight ratio of the pretreated potato starch residue to the PBAT is (5:5) to (6:4).
8. A potato starch residue reinforced PBAT biodegradable injection molding material, characterized in that: The material is prepared by the method for preparing the potato starch residue reinforced PBAT biodegradable injection molding material according to any one of claims 1 to 7.
9. An application of a potato starch residue reinforced PBAT biodegradable injection molding material, characterized in that: The biodegradable injection molding material as claimed in claim 8 is used in plastic production.
Citation Information
Patent Citations
Method for producing degradable plastic from bagasse
CN113234327A